Patterns and uses of mezzanine of low cost apartments in Surabaya - Rika Kisnarini (Institut Teknologi Sepuluh Nopember, 2017)
Dwelling today should provide an opportunity for residents to develop. The design of storey residential buildings including apartments for low-income community should be thought about how these poor families are also developing therefore their space requirement is also growing. Rusunawa in Surabaya is a simple multi-storey dwelling which is built to accommodate disadvantaged households. Usually the available space comprising: a multi-functional space, a kitchen, a bathroom / WC, and sometimes completed with a balcony. The space that can be lived in here is only the multi-functional space. So, only in this space the family take care all their activities both the private activities such as sleeping and storing money, as well as public activities such as entertaining, watching TV etc. Addition space at least for separating between their private and public activities is exactly needed. In this case, beside by partitioning, separating the multi-functional space by constructing a mezzanine is the best and most legal way for creating additional (private) space. This study aims to investigate the patterns and whatever uses of space that can be made by household residents of low cost apartments in Surabaya for their mezzanine dealing with their adapting action in meeting their spatial demands. A hundred of users living in Rusunawa spreading out in 14 locations in Surabaya are taken as samples. The methods applied are questionnaires and checklist. Results of study expected are patterns and uses of mezzanine